2011
DOI: 10.1093/jxb/err158
|View full text |Cite
|
Sign up to set email alerts
|

The aromatic/arginine selectivity filter of NIP aquaporins plays a critical role in substrate selectivity for silicon, boron, and arsenic

Abstract: Nodulin-26-like intrinsic proteins (NIPs) of the aquaporin family are involved in the transport of diverse solutes, but the mechanisms controlling the selectivity of transport substrates are poorly understood. The purpose of this study was to investigate how the aromatic/arginine (ar/R) selectivity filter influences the substrate selectivity of two NIP aquaporins; the silicic acid (Si) transporter OsLsi1 (OsNIP2;1) from rice and the boric acid (B) transporter AtNIP5;1 from Arabidopsis; both proteins are also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
187
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(193 citation statements)
references
References 33 publications
5
187
0
1
Order By: Relevance
“…Conserved residues of the NPA domain and ar/R selectivity filter (Murata et al 2000;Hub and de Groot 2008;Mitani-Ueno et al 2011) were identified by multiple sequence alignment with MUSCLE of the different sub-families of P. vulgaris aquaporins together with the tomato aquaporins identified by Reuscher et al (2013). Prediction of transmembrane domains was performed using TMHMM server v.2.0, using default parameters (http://www.cbs.dtu.dk/services/TMHMM/) (Krogh et al 2001).…”
Section: Sub-cellular Localizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Conserved residues of the NPA domain and ar/R selectivity filter (Murata et al 2000;Hub and de Groot 2008;Mitani-Ueno et al 2011) were identified by multiple sequence alignment with MUSCLE of the different sub-families of P. vulgaris aquaporins together with the tomato aquaporins identified by Reuscher et al (2013). Prediction of transmembrane domains was performed using TMHMM server v.2.0, using default parameters (http://www.cbs.dtu.dk/services/TMHMM/) (Krogh et al 2001).…”
Section: Sub-cellular Localizationmentioning
confidence: 99%
“…This aquaporin is also able to transport arsenite and boric acid when expressed in Xenopus oocytes. Mutation in the H5 position of the ar/R selectivity filter resulted in a loss of transport activity for these molecules (Mitani-Ueno et al 2011). On the other hand, a G to A mutation in the H2 position of the ar/R selectivity filter does not affect the transport 15 capability of this protein (Mitani-Ueno et al 2011).…”
Section: ; Magadum Et Al 2013) Duplicated Genes Could Undergo Pmentioning
confidence: 99%
See 2 more Smart Citations
“…HvPIP2 has been shown to transport water and have the ability to mediate water loss from plant cells under salt stress (Horie et al, 2011). NIPs only exist in plants and can transport different substrates, not only water, glycerol (Dean et al, 1999), and lactic acid (Choi and Roberts, 2007) but also large solutes such as urea (Wallace and Roberts, 2005), boron, silicon, and arsenic (Mitani-Ueno et al, 2011). TaNIP (Triticum asetivum L. nodulin 26-like intrinsic protein) has been reported to be associated with salt tolerance pathways in plants (Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%